2020
DOI: 10.1097/psy.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adversity and Pubertal Development Among Puerto Rican Boys and Girls

Abstract: Objective Evidence stemming largely from retrospective studies suggests that childhood adversity (CA) is associated with earlier age at menarche, a marker of pubertal timing, among girls. Little is known about associations with pubertal tempo among boys or racial/ethnic minorities. We examined the association between CA and timing and tempo of pubertal development among boys and girls. Methods The Boricua Youth Study is a longitudinal study of Puerto Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…It is possible that if we had continued to follow these boys into their teenage years those with more trauma exposure would display faster pubertal tempo relative to those with low or no trauma. However, our results parallel those from a growing number of studies that report slower pubertal timing in boys who experience more ELS relative to those who experience less (Semiz et al, 2009;Johnson et al, 2018;Suglia et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It is possible that if we had continued to follow these boys into their teenage years those with more trauma exposure would display faster pubertal tempo relative to those with low or no trauma. However, our results parallel those from a growing number of studies that report slower pubertal timing in boys who experience more ELS relative to those who experience less (Semiz et al, 2009;Johnson et al, 2018;Suglia et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that our measurement of puberty may have been less reliable for boys, perhaps in part because of their relatively early pubertal development. However, prior studies have also reported that ELS is linked to earlier pubertal timing in girls but delayed timing in boys from three different populations (Semiz et al, 2009;Johnson et al, 2018;Suglia et al, 2020). Studies that examine the associations between trauma, pubertal timing, and mental health in Black girls and boys at equivalent stages of development are needed to determine if the present results reflect true sex differences in the association between trauma and puberty or are an artifact of testing girls and boys at different stages of puberty.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations